Gashaka Gumti National Park Tourism Development and Biodiversity Conservation - Madaki, Kanati; Umaru, Isaac John; Umaru, Kerenhapucch Isaac (Darul Yasin Al Sys, 2024)
Tourist activities in host environments often create land use problems, such as infrastructure development, and damage to ecosystems and habitats. These disturbances can lead to the disruption of wildlife species, affecting their normal behavior, increasing mortality, and reducing reproductive success. Despite these challenges, the direct benefits of tourism development to the local community are substantial. The study found that 76.06% of locals engaged in merchandise sales, 77.66% gained employment through park development, and 52.6% participated in tourism-related activities. Additionally, the indirect benefits of tourism development to the local community include increased security, improved wildlife conservation, enhanced infrastructure development, employment opportunities, and increased wildlife knowledge, with an average significance ranging from 26% to 45%. In conclusion, tourism development and biodiversity conservation contribute significantly to development, knowledge, employment, and awareness within the local community and the country at large.